Estill Voice TrainingTM - A Popular Approach to Voice Training - Kateřina Jehličková (Listy klinicke logopedie)
Estill Voice TrainingTM (EVT) is a voice training method based on the understanding of how the vocal mechanism works. This method offers an effective approach to voice development, re-education, and rehabilitation, making it valuable also in speech therapy practice. This article introduces the fundamentals of EVT, its principles and benefits, and provides a brief overview of the key techniques.